Information Technology Utilization and the Role of Improving Taxpayer Compliance - Lestari, Utami Puji; Sinambela, Ella Anastasya (Metromedia, 2022)
Taxes play an important role in contributing to state revenue so that taxes have urgency as the main part in supporting all forms of financing in state governance including state development in Indonesia. This research aims to explain the optimization of the role of information technology in supporting taxpayer compliance in Indonesia. In addition, this study also analyzes the transformation of digital technology used by the Directorate General of Taxes as a tax collector as an effort to increase taxpayer awareness in Indonesia. The research method applied is using quantitative methods with the analysis used is simple regression. The population in this study were taxpayers in the city of Surabaya and sampling was convenience sampling with 63 taxpayers as respondents. The results of this study reveal that information technology has a role in supporting taxpayer compliance. The role of information technology is proven to have a considerable impact in increasing taxpayer awareness to pay taxes so that the increase in state revenue through tax collection also increases every year.